Advanced Bio‐Based UV‐Curable Anticorrosive Coatings Reinforced by hBN. Issue 40 (30th October 2018) - Zhao, Hongran; Ding, Jiheng; Yu, Haibin
Abstract: Here, furfuryl methacrylate (FAM) was first successfully synthesized. Bulk hexagonal boron nitride (hBN) nanosheets were exfoliated and dispersed in FAM based on the strong π‐π interaction between hBN and FAM. The few‐layer hBN nanosheets as‐prepared possessed an average thickness of ∼3 nm (less than 10 layers) and exhibited superior storage stabilization under environment condition in FAM. Moreover, we creatively applied FAM solutions containing 0.25‐0.75 wt% of hBN as reactive diluents for the epoxidized soybean oil methacrylate (ESOM) matrix to effectively enhance its corrosion protection by suppressing the penetration of aggressive species. The electrochemical results revealed that the impedance of the coating containing 0.75 wt. % hBN is ∼200 times bigger than that of the blank coating specimen. Abstract : A green method has been developed to prepare extremely concentrated few layersfurfuryl methacrylate stabilzed hBN (FAM/hBN) solution. FAM/hBN is available for the reinforcement of barrier properties in UV‐curable epoxidized soybean oil methacrylate (ESOM) coatings. This strategy gives a great potential for the advanced applications of hBN reinforced UV‐curable ESOM coatings, which facilitates the large‐scale fabrication of hBN‐based UV‐curable coatings with high anticorrosion properties.